Flaky rare earth-based molybdate ceramic material and preparation method thereof
Through electrospinning method and ceramicized heat treatment process, two-dimensional thin flaky rare earth-based molybdate ceramic materials with nano-thickness were prepared, which solved the problems of large particle size and uncontrollable morphology in the prior art, and improved the catalysis of the materials Performance and scope of application.
Patent Information
- Application Number
- CN202411294845.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-14
AI Technical Summary
It is difficult to prepare two-dimensional thin flaky rare earth-based molybdate ceramic materials with nano-thickness, and the prepared Re2MoO6 powder has a large particle size and uncontrollable morphology, which limits its application in the fields of catalysis and luminescence.
Electrospinning combined with ceramicized heat treatment process was used to prepare two-dimensional thin flaky rare earth-based molybdate ceramic materials with nano-thickness. By optimizing the ceramicized heat treatment temperature and time, the complete transformation and structural control of the material are ensured.
The flaky rare earth-based molybdate ceramic material with controllable thickness was successfully prepared, which improved its specific surface area and catalytic performance, solved the problems of easy agglomeration and low dimensional accuracy of nanomolybdate ceramic powder particles, and broadened its catalytic, Applications in the fields of luminescence and other fields.
Smart Images

Figure CN119241237A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and relates to a flaky rare earth-based molybdate ceramic material and a preparation method thereof, and specifically relates to a two-dimensional flaky rare earth-based molybdate ceramic material with nanometer thickness and a preparation method thereof. Background Art
[0002] Rare Earth Molybdate Re 2 MoO 6 (Re is selected from La, Ce, Pr, Eu, Ho, Er, Yb or Tm) has excellent thermal stability, chemical stability and wide excitation band, and has broad application prospects in catalysis, luminescence, energy and other fields. A large number of studies have shown that the influence of rare earth molybdate Re 2 MoO 6 The main factors affecting performance are the selection and combination of rare earth elements and the structural morphology of the crystal. Due to the differences in the electronic structures of different rare earth elements, the transfer and absorption efficiency of their excitation energy are also different. Therefore, by optimizing the composition of rare earth elements, the Re 2 MoO 6 In addition, the preparation of nanoscale Re 2 MoO 6 By adjusting its crystal structure and morphology, a larger specific surface area can be obtained, thereby exposing more active sites and improving the catalytic and optical properties of the material.
[0003] At present, the commonly used Re 2 MoO 6 There are two main preparation methods: high temperature solid phase method and precipitation method. Among them, the high temperature solid phase method has become the most popular method for preparing Re due to its abundant raw materials and simple preparation process. 2 MoO 6 However, the Re 2 MoO 6 The powder particle size is large (usually ranging from a few microns to tens of microns), and the morphology of the powder particles is uncontrollable. 2 MoO 6 , but the Re prepared by this method 2 MoO 6 Powder particles have defects such as easy agglomeration and low dimensional accuracy, so they usually need to be combined with other materials to be used, which limits their application development. However, there is no report on the preparation of two-dimensional thin-sheet rare earth-based molybdate ceramic materials with nanometer thickness. Summary of the invention
[0004] In order to improve the above technical problems, the present invention provides a flaky rare earth-based molybdate ceramic material and a preparation method thereof. The present invention adopts an electrospinning method combined with ceramic heat treatment and other processes to prepare a ceramic material having a two-dimensional thin sheet structure with a nanometer thickness, thereby broadening its application in catalysis, luminescence and other fields.
[0005] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:
[0006] A flaky rare earth-based molybdate ceramic material, the ceramic material is a two-dimensional flaky structure, preferably an irregularly shaped two-dimensional flaky structure, more preferably a two-dimensional thin flaky structure. Preferably, the flaky rare earth-based molybdate ceramic material has a thickness of 5 to 30 nm, for example, 5-15 nm, 10-20 nm, 20-30 nm.
[0007] According to the present invention, the chemical formula of the flaky rare earth-based molybdate ceramic material is Re 2 MoO 6 , wherein: Re is selected from one, two or more of La, Y, Ce, Pr, Eu, Ho, Er, Yb, and Tm, and preferably five of the above elements.
[0008] Preferably, the rare earth elements in the flaky rare earth-based molybdate ceramic material are evenly distributed.
[0009] According to the present invention, the flaky rare earth-based molybdate ceramic material is prepared by electrospinning a precursor solution including a Re source, a Mo source and a spinning aid to obtain a precursor film, which is then subjected to a ceramicization heat treatment.
[0010] The present invention also provides a method for preparing the above-mentioned flaky rare earth-based molybdate ceramic material, comprising preparing a precursor film by electrostatic spinning from a precursor solution containing a Re source, a Mo source and a spinning aid, and then preparing the flaky rare earth-based molybdate ceramic material by ceramic heat treatment.
[0011] According to the present invention, the Re source is selected from salts containing Re elements, preferably nitrates containing Re elements; wherein: Re is selected from one, two or more of La, Y, Ce, Pr, Eu, Ho, Er, Yb, and Tm, preferably five of the above elements.
[0012] According to the present invention, the Mo source is selected from a salt containing the Mo element, for example, selected from MoCl 5 or molybdenum nitrate (Mo(NO 3 ) 2 ).
[0013] According to the present invention, the spinning aid is polyvinyl pyrrolidone (PVP).
[0014] According to the present invention, the concentration of the spinning aid in the precursor solution is 1-10%, exemplified by 1%, 2%, 5%, 8%, and 10%.
[0015] According to the present invention, the solvent used in the precursor solution is at least one of anhydrous ethanol and N,N-dimethylformamide (DMF). Preferably, when the solvent is a composite of two solvents, the mass ratio of the two is 1:(0.5-2), exemplified by 1:1.2, 1:1.4, 1:1.5.
[0016] According to the present invention, the voltage of the electrospinning method is 10-20 kV, exemplarily 20 kV; the feed rate of the electrospinning method is 0.4-1.2 mL / h -1 , exemplarily 0.6 ml / h; the spinning distance of the electrospinning method is 10-15 cm, exemplarily 12 cm; the relative humidity of the electrospinning environment is (30±3)% and the temperature is (25±3)°C.
[0017] According to the present invention, the temperature of the ceramic heat treatment is 600-800°C, preferably 700-800°C, and exemplarily 750°C; the constant temperature time of the ceramic heat treatment is 1-4h, and exemplarily 2h; the heating rate of the ceramic heat treatment is 0.1-5°C / min, and exemplarily 1°C / min.
[0018] The applicant unexpectedly discovered through a large number of experiments that when the temperature of the ceramic heat treatment is 650°C, the Re 2 MoO 6 The ceramic material contains other phase components, indicating that the precursor has not been completely transformed into Re 2 MoO 6 When the ceramic heat treatment temperature rises to 700-800℃, the precursor is completely transformed into Re 2 MoO 6 When the temperature of ceramic heat treatment is higher than 800℃, Re 2 MoO 6 The grains will grow significantly and no longer present a flaky structure. Therefore, in the present invention, the temperature of the ceramic heat treatment is preferably 700-800°C.
[0019] According to the present invention, the method for preparing the flaky rare earth-based molybdate ceramic material comprises the following steps:
[0020] (1) Add a Re source (such as Re(NO)) in a stoichiometric ratio. 3 ) 3 6H 2 O) and Mo source (such as MoCl 5) (the molar ratio of Re element to Mo element is 2:1) is added to the solvent, and then a spinning aid (such as PVP) is added to obtain a precursor solution that can be electrospun;
[0021] (2) spinning the precursor solution obtained in step (1) (loaded into an electrospinning machine), and collecting the precursor film after the spinning is completed;
[0022] (3) drying the precursor film prepared in step (2), subjecting it to a ceramic heat treatment, and obtaining a sheet-like Re 2 MoO 6 Ceramic material.
[0023] In one embodiment of the present invention, the drying temperature is 40-100°C, and exemplarily 60°C.
[0024] The present invention also provides the application of the above-mentioned flaky rare earth-based molybdate ceramic material in the fields of catalysis, luminescence, energy, etc.
[0025] The invention also provides a catalyst, which contains the above-mentioned flaky rare earth-based molybdate ceramic material.
[0026] Beneficial effects of the present invention:
[0027] The present invention adopts a process method combining electrospinning with ceramic heat treatment to successfully prepare a flaky rare earth-based molybdate ceramic material for the first time. The flaky rare earth-based molybdate ceramic material prepared by the present invention has a nanometer thickness and can controllably adjust the thickness of the flaky rare earth-based molybdate ceramic material to obtain a larger specific surface area, thereby exposing more active sites to improve the catalytic performance and optical properties of the material. Compared with the existing preparation method, the present invention effectively solves the shortcomings of easy agglomeration of nano-molybdate ceramic powder particles and low dimensional accuracy. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a sheet (LaYErHoTm) prepared according to Example 1 2 MoO 6 Ceramic morphology (SEM photo).
[0029] Figure 2 It is a sheet (LaYErHoTm) prepared according to Example 2 2 MoO 6 Ceramic morphology (SEM photo).
[0030] Figure 3 It is a sheet (LaYErHoTm) prepared according to Example 3 2 MoO 6 Ceramic morphology (SEM photo).
[0031] Figure 4 It is a sheet (LaYErHoTm) prepared according to Example 3 2 MoO 6 Ceramic XRD pattern.
[0032] Figure 5 This is a schematic diagram of the preparation of flaky rare earth-based molybdate ceramic materials. DETAILED DESCRIPTION
[0033] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention, and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0034] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0035] Example 1
[0036] A method for preparing a flaky rare earth-based molybdate ceramic material comprises the following steps:
[0037] (1) Weigh 0.0004 mol of La(NO 3 ) 3 6H 2 O, 0.0004 mol of Y(NO 3 ) 3 6H 2 O, 0.0004 mol Ho(NO 3 ) 3 6H 2 O, 0.0004 mol of Er(NO 3 ) 3 6H 2 O, 0.0004mol Tm(NO 3 ) 3 6H 2 O and 0.001 molMoCl 5 Add it to a beaker of a mixed solution of 5g anhydrous ethanol and 7g N,N-dimethylformamide, and then stir it magnetically to dissolve. After the solution is clarified, add 1g polyvinyl pyrrolidone (PVP) and stir it magnetically. After the mixture is completely dissolved, the desired electrospinning precursor solution is obtained.
[0038] (2) The electrospinning solution prepared in step (1) is loaded into a spinning machine for spinning. The spinning voltage is 20 kV, the spinning distance is 12 cm, the injection pump propulsion speed is 0.6 ml / h, the ambient humidity is 30%, and the spinning temperature is 25°C. After the spinning is completed, the precursor film can be collected.
[0039] (3) The precursor film obtained in step (2) is placed in a 60°C oven for drying, and then placed in a 750°C muffle furnace for ceramic heat treatment. The heat treatment time is 2 hours and the heating rate is 1°C / min. After cooling to room temperature, a sheet of (LaYErHoTm) can be obtained. 2 MoO 6 ceramics.
[0040] Figure 1 (LaYErHoTm) prepared in this embodiment 2 MoO 6 Scanning electron microscope (SEM) image of ceramics. From the image, we can see that the ceramic material is a large, integral sheet structure with a thickness of 20-30nm, and a small amount of fiber filaments are mixed in the middle.
[0041] Example 2
[0042] A method for preparing a flaky rare earth-based molybdate ceramic material comprises the following steps:
[0043] (1) Weigh 0.0004 mol of La(NO 3 ) 3 6H 2 O, 0.0004 mol of Y(NO 3 ) 3 6H 2 O, 0.0004 mol Ho(NO 3 ) 3 6H 2 O, 0.0004 mol of Er(NO 3 ) 3 6H 2 O, 0.0004mol Tm(NO 3 ) 3 6H 2 O and 0.001 molMoCl 5 Add it to a beaker of a mixed solution of 5g anhydrous ethanol and 6g N,N-dimethylformamide, and then stir it magnetically to dissolve. After the solution is clarified, add 0.9g polyvinyl pyrrolidone (PVP) and stir it magnetically. After the mixture is completely dissolved, the desired electrospinning precursor solution is obtained.
[0044] (2) The electrospinning solution prepared in step (1) is loaded into a spinning machine for spinning. The spinning voltage is 20 kV, the spinning distance is 12 cm, the injection pump propulsion speed is 0.6 ml / h, the ambient humidity is 30%, and the spinning temperature is 25°C. After the spinning is completed, the precursor film can be collected.
[0045] (3) The precursor film obtained in step (2) is placed in a 60°C oven for drying, and then placed in a 750°C muffle furnace for ceramic heat treatment. The heat treatment time is 2 hours and the heating rate is 1°C / min. After cooling to room temperature, a sheet of (LaYErHoTm) can be obtained. 2 MoO 6 ceramics.
[0046] Figure 2 (LaYErHoTm) prepared in this embodiment 2 MoO 6 The SEM image of the ceramic shows that the ceramic material is an irregularly shaped sheet structure with a thickness of 10-20 nm. Compared with Example 1, the ceramic material prepared in this example is a dispersed sheet structure with a reduced thickness and no fiber filaments are mixed therein.
[0047] Example 3
[0048] A method for preparing a flaky rare earth-based molybdate ceramic material comprises the following steps:
[0049] (1) Weigh 0.0004 mol of La(NO 3 ) 3 6H 2 O, 0.0004 mol of Y(NO 3 ) 3 6H 2 O, 0.0004 mol Ho(NO 3 ) 3 6H 2 O, 0.0004 mol of Er(NO 3 ) 3 6H 2 O, 0.0004mol Tm(NO 3 ) 3 6H 2 O and 0.001 molMoCl 5 Add it to a beaker of a mixed solution of 4g anhydrous ethanol and 6g N,N-dimethylformamide, and then stir it magnetically to dissolve. After the solution is clarified, add 0.8g polyvinyl pyrrolidone (PVP) and stir it magnetically. After the mixture is completely dissolved, the desired electrospinning precursor solution is obtained.
[0050] (2) The electrospinning solution prepared in step (1) is loaded into a spinning machine for spinning. The spinning voltage is 20 kV, the spinning distance is 12 cm, the injection pump propulsion speed is 0.6 ml / h, the ambient humidity is 30%, and the spinning temperature is 25°C. After the spinning is completed, the precursor film can be collected.
[0051] (3) The precursor film obtained in step (2) is placed in a 60°C oven for drying, and then placed in a 750°C muffle furnace for ceramic heat treatment. The heat treatment time is 2 hours and the heating rate is 1°C / min. After cooling to room temperature, a sheet of (LaYErHoTm) can be obtained. 2 MoO 6 ceramics.
[0052] Figure 3 (LaYErHoTm) prepared in this embodiment 2 MoO 6 The scanning electron microscope (SEM) image of the ceramic shows that the ceramic material is an irregularly shaped sheet structure with a thickness of 5-15 nm. Compared with Examples 1 and 2, the ceramic material prepared in this example is a dispersed sheet structure with a further reduced thickness and no fiber filaments are mixed therein.
[0053] Figure 4 It is the flake (LaYErHoTm) prepared in Example 3 2 MoO 6 XRD patterns of ceramics.
[0054] Example 4
[0055] A method for preparing a flaky rare earth-based molybdate ceramic material comprises the following steps:
[0056] (1) Weigh 0.0004 mol of La(NO 3 ) 3 6H 2 O, 0.0004 mol Y(NO 3 ) 3 6H 2 O, 0.0004molHo(NO 3 ) 3 6H 2 O, 0.0004 mol Er(NO 3 ) 3 6H 2 O, 0.0004mol Tm(NO 3 ) 3 6H 2 O and 0.001 molMoCl 5Add it to a beaker of a mixed solution of 4g anhydrous ethanol and 6g N,N-dimethylformamide, and then stir it magnetically to dissolve. After the solution is clarified, add 0.8g polyvinyl pyrrolidone (PVP) and stir it magnetically. After the mixture is completely dissolved, the desired electrospinning precursor solution is obtained.
[0057] (2) The electrospinning solution prepared in step (1) is loaded into a spinning machine for spinning. The spinning voltage is 20 kV, the spinning distance is 12 cm, the injection pump propulsion speed is 0.6 ml / h, the ambient humidity is 30%, and the spinning temperature is 25°C. After the spinning is completed, the precursor film can be collected.
[0058] (3) The precursor film obtained in step (2) is placed in a 60°C oven for drying, and then placed in a 650°C muffle furnace for ceramic heat treatment. The heat treatment time is 2 hours and the heating rate is 1°C / min. After cooling to room temperature, a sheet of (LaYErHoTm) can be obtained. 2 MoO 6 ceramics.
[0059] When the ceramic heat treatment is carried out at this temperature, the precursor film is not completely transformed into (LaYErHoTm) 2 MoO 6 Ceramic phase, and also contains intermediate phases.
[0060] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A flaky rare earth-based molybdate ceramic material, characterized in that: The ceramic material is a two-dimensional sheet structure, preferably a two-dimensional thin sheet structure. Preferably, the thickness of the flaky rare earth-based molybdate ceramic material is 10-30 nm.
2. The ceramic material according to claim 1, characterized in that The chemical formula of the flaky rare earth-based molybdate ceramic material is Re2MoO6, wherein: Re is selected from one, two or more of La, Ce, Pr, Eu, Ho, Er, Yb, and Tm, preferably five of the above elements. Preferably, the rare earth elements in the flaky rare earth-based molybdate ceramic material are evenly distributed.
3. The method for preparing a ceramic material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the steps of preparing a precursor film from a precursor solution containing a Re source, a Mo source and a spinning aid by an electrostatic spinning method, and then preparing a flaky rare earth-based molybdate ceramic material by ceramic heat treatment.
4. The preparation method according to claim 3, characterized in that: The Re source is selected from salts containing Re elements, preferably nitrates containing Re elements; wherein: Re is selected from one, two or more of La, Y, Ce, Pr, Eu, Ho, Er, Yb, and Tm, preferably five of the above elements. Preferably, the Mo source is selected from a salt containing the Mo element, for example, selected from MoCl5 or molybdenum nitrate (Mo(NO3)2).
5. The preparation method according to claim 3, characterized in that: The spinning aid is polyvinyl pyrrolidone (PVP). Preferably, the concentration of the spinning aid in the precursor solution is 1-10%. Preferably, the solvent used in the precursor solution is at least one of anhydrous ethanol and DMF. Preferably, when the solvent is a composite of two solvents, the mass ratio of the two solvents is 1:(0.5-2).
6. The preparation method according to claim 3, characterized in that: The voltage of the electrospinning method is 10-20 kV; the feed rate of the electrospinning method is 0.4-1.2 mL / h -1 ; The spinning distance of the electrospinning method is 10-15cm.
7. The preparation method according to claim 3, characterized in that: The temperature of the ceramic heat treatment is 600-800°C, preferably 700-800°C; the constant temperature time of the ceramic heat treatment is 1-4h; the heating rate of the ceramic heat treatment is 0.1-5°C / min.
8. The preparation method according to any one of claims 3 to 7, characterized in that: The method for preparing the flaky rare earth-based molybdate ceramic material comprises the following steps: (1) adding a Re source and a Mo source into a solvent in a stoichiometric ratio, and then adding a spinning aid to obtain a precursor solution capable of electrospinning; (2) spinning the precursor solution obtained in step (1), and collecting the precursor film after the spinning is completed; (3) Drying and ceramicizing the precursor film prepared in step (2), and obtaining a flaky Re2MoO6 ceramic material after the heat treatment.
9. Application of the flaky rare earth-based molybdate ceramic material according to any one of claims 1 to 2 and / or the flaky rare earth-based molybdate ceramic material prepared by the preparation method according to any one of claims 3 to 7 in the fields of catalysis, luminescence, energy, etc.
10. A catalyst, characterized in that The invention contains the flaky rare earth-based molybdate ceramic material according to any one of claims 1 to 3 and / or the flaky rare earth-based molybdate ceramic material prepared by the preparation method according to any one of claims 3 to 7.
Citation Information
Patent Citations
Preparation method for square strontium molybdate nano-plate
CN101659445A
Rare earth molybdate ultrathin film material with controllable morphology and preparation method thereof
CN106115782A
Membrane made of a nanostructured material
US20100233812A1
Infrared selective radiation cooling nano-functional composition and preparation method therefor
WO2021017524A1
Method for preparing oxide high-entropy ceramic fibers
WO2022247346A1
